A multicentre, UK, retrospective, observational study to assess the effectiveness of insulin glargine 300 units/ml in treating people with Type 1 diabetes mellitus in routine clinical practice (SPARTA). Issue 1 (16th November 2018) - Pang, T.; Bain, S. C.; Black, R. Neil A.; Boyle, J. G.; Elliott, J.; Holcombe, A.; Lee, K. C. S.; Mulligan, C.; Saunders, L.; Yousseif, A.; Baxter, M.
Abstract: Aim: To conduct an open‐label study to provide UK real‐world evidence regarding the use of insulin glargine 300 units/ml (U300) in people with Type 1 diabetes mellitus. Methods: People with Type 1 diabetes who had been prescribed U300 ≥6 months before data collection and had HbA1c levels recorded within 3 months prior to U300 (baseline) were included. The primary endpoint was change in HbA1c from baseline to month 6 after U300 initiation. Other endpoints included number of documented hypoglycaemic and diabetic ketoacidosis episodes, and change in daily basal insulin dose. Results: A total of 298 people with Type 1 diabetes were included [mean age 42.1 years, mean HbA1c 79 mmol/mol (9.4%)]. After U300 initiation, the mean reduction in HbA1c from baseline to month 6 was –4 mmol/mol (–0.4%; P <0.001; n =188). The total daily basal insulin dose at 6 months was 1.3 units higher than at the time of U300 initiation ( P <0.001; n =275) but was not significantly different from the prior basal insulin dose. There was no clinically significant difference in weight between baseline and month 6 [mean difference +0.7 kg, 95% CI –0.1, 1.5; P =0.084; n =115). During the 6 months before and after U300 initiation, severe hypoglycaemic episodes were documented for 6/298 and 4/298 participants. Diabetic ketoacidosis episodes requiring Accident and Emergency department visits or hospitalization were documented for 4/298 and 6/298 participants, before and after U300 initiation, respectively. Conclusions: In people with Type 1 diabetes, a change in basal insulin to U300 was associated with clinically and statistically significant HbA1c improvements, without significant changes in basal insulin dose and weight. Documented severe hypoglycaemia episodes and diabetic ketoacidosis requiring Accident and Emergency department visits or hospitalization were low and similar before and after U300 initiation. What's new?: This descriptive, retrospective study provides real‐world data on the use of a second‐generation basal insulin, insulin glargine 300 units/ml (U300), in Type 1 diabetes across the UK. Overall, participants who switched to U300 demonstrated improvements in HbA1c without significant changes in basal insulin dose and weight from baseline. The number of participants with documented severe hypoglycaemia and ketoacidosis requiring Accident and Emergency department visits or hospitalization was low and similar prior to and after U300 initiation. Results from this real‐world study show that observations made in randomized controlled trials translate to people with Type 1 diabetes treated with U300 in clinical practice in the UK.